A supramolecular pyrenyl glycoside-coated 2D MoS2 composite electrode for selective cell capture. Issue 78 (9th September 2016) - Wahiba, Mokhtari; Feng, Xue-Qing; Zang, Yi; James, Tony D.; Li, Jia; Chen, Guo-Rong; He, Xiao-Peng
Abstract : We show the construction of a supramolecular 2D MoS2 glycocomposite for the selective capture of cells that highly express a glycoprotein receptor on an electrode surface. Abstract : Here we demonstrate the simple construction and characterization of a pyrenyl glycoside-coated 2D MoS2 material composite capable of selectively capturing proteins and live cells on an electrode, as determined by differential pulse voltammetry.